Kuoxin Decoction promotes lymphangiogenesis in zebrafish and in vitro based on network analysis - Longping Peng; Mengjiao Ma; Yidan Dong; Qiong Wu; Shiying An; Min Cao; Yi Wang; Chang Zhou; Maolin Zhou; Xu Wang; Qianqian Liang; Qianqian Liang; et al. (Frontiers Media S.A., 2022)
Background: Inadequate lymphangiogenesis is closely related to the occurrence of many kinds of diseases, and one of the important treatments is to promote lymphangiogenesis. Kuoxin Decoction (KXF) is an herbal formula from traditional Chinese medicine used to treat dilated cardiomyopathy (DCM), which is associated with lymphangiogenesis deficiency. In this study, we comprehensively verified whether KXF promotes lymphangiogenesis in zebrafish and in vitro based on network analysis.Methods: We performed virtual screening of the active compounds of KXF and potential targets regarding DCM based on network analysis. Tg (Flila: EGFP; Gata1: DsRed) transgenic zebrafish embryos were treated with different concentrations of KXF for 48 h with or without the pretreatment of MAZ51 for 6 h, followed by morphological observation of the lymphatic vessels and an assessment of lymphopoiesis. RT-qPCR was employed to identify VEGF-C, VEGF-A, PROX1, and LYVE-1 mRNA expression levels in different groups. After the treatment of lymphatic endothelial cells (LECs) with different concentrations of salvianolic acid B (SAB, the active ingredient of KXF), their proliferation, migration, and protein expression of VEGF-C and VEGFR-3 were compared by CCK-8 assay, wound healing assay, and western blot.Results: A total of 106 active compounds were identified constituting KXF, and 58 target genes of KXF for DCM were identified. There were 132 pathways generated from KEGG enrichment, including 5 signaling pathways related to lymphangiogenesis. Zebrafish experiments confirmed that KXF promoted lymphangiogenesis and increased VEGF-C and VEGF-A mRNA expression levels in zebrafish with or without MAZ51-induced thoracic duct injury. In LECs, SAB promoted proliferation and migration, and it could upregulate the protein expression of VEGF-C and VEGFR-3 in LECs after injury.Conclusion: The results of network analysis showed that KXF could regulate lymphangiogenesis through VEGF-C and VEGF-A, and experiments with zebrafish confirmed that KXF could promote lymphangiogenesis. Cell experiments confirmed that SAB could promote the proliferation and migration of LECs and upregulate the protein expression of VEGF-C and VEGFR-3. These results suggest that KXF promotes lymphangiogenesis by a mechanism related to the upregulation of VEGF-C/VEGFR-3, and the main component exerting this effect may be SAB.